2010
DOI: 10.1088/0004-637x/713/1/410
|View full text |Cite
|
Sign up to set email alerts
|

The Crires Search for Planets Around the Lowest-Mass Stars. I. High-Precision Near-Infrared Radial Velocities With an Ammonia Gas Cell

Abstract: Radial velocities measured from near-infrared spectra are a potentially powerful tool to search for planets around cool stars and sub-stellar objects. However, no technique currently exists that yields near-infrared radial velocity precision comparable to that routinely obtained in the visible. We are carrying out a near-infrared radial velocity planet search program targeting a sample of the lowestmass M dwarfs using the CRIRES instrument on the VLT. In this first paper in a planned series about the project, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
154
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(159 citation statements)
references
References 52 publications
3
154
0
Order By: Relevance
“…In addition, Mahadevan & Ge (2009) reported on a mixture that produces a dense absorption spectrum in the H band. Bean et al (2010) reported that for their CRIRES survey consisting of a search for planets around M-dwarfs, they reach a RV precision of 5 m s −1 using a NH 3 gas cell in the K band. A similar strategy for wavelength calibration is the use of telluric lines in the NIR as a natural gas cell.…”
Section: Instrumental Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Mahadevan & Ge (2009) reported on a mixture that produces a dense absorption spectrum in the H band. Bean et al (2010) reported that for their CRIRES survey consisting of a search for planets around M-dwarfs, they reach a RV precision of 5 m s −1 using a NH 3 gas cell in the K band. A similar strategy for wavelength calibration is the use of telluric lines in the NIR as a natural gas cell.…”
Section: Instrumental Limitationsmentioning
confidence: 99%
“…Usually, the PSF of the spectrograph is close to a Gaussian function, but it can be slightly asymmetric (e.g. Endl et al 2000;Bean et al 2010). In our simulations, we adopted a Gaussian function as the PSF of the spectrograph.…”
Section: Creating the Data Setsmentioning
confidence: 99%
“…As an example, iodine gas cells, which have been used extensively as wavelength calibrators in optical RV surveys, do not offer a sufficient density of absorption lines in the NIR domain. For this reason, most existing NIR RV studies have used telluric lines to achieve wavelength calibration (Blake et al 2010;Crockett et al 2011;Bailey et al 2012;Tanner et al 2012;Davison et al 2015), with the exception of Bean et al (2010), who used an ammonia gas cell with CRyogenic high-resolution InfraRed Echelle Spectrograph (CRIRES) at the VLT to obtain unprecedented long-term precisions of ≈5-10 m s −1 in the NIR on targets with K S -band magnitudes between 4.4 and 8.0.…”
Section: Introductionmentioning
confidence: 99%
“…Planets with masses between 1 and 10 M Earth , ''super-Earths,'' have indeed been detected in the last few years around low-mass stars, such as Gl 581 d and Gl 667C c by radial velocity (Udry et al, 2007;Mayor et al, 2009;Vogt et al, 2010;Bonfils et al, 2011;Forveille et al, 2011;AngladaEscudé et al, 2012;Delfosse et al, 2012) and GJ 1214 b by transit (Charbonneau et al, 2009;Sada et al, 2010;Carter et al, 2011;Kundurthy et al, 2011). Several observational campaigns designed specifically to detect planets around low-mass stars are now underway (Nutzman and Charbonneau, 2008;Boss et al, 2009;Zechmeister et al, 2009;Bean et al, 2010;Rodler et al, 2011).…”
Section: Introductionmentioning
confidence: 99%